2010
DOI: 10.1186/1471-244x-10-45
|View full text |Cite
|
Sign up to set email alerts
|

Post-injection delirium/sedation syndrome in patients with schizophrenia treated with olanzapine long-acting injection, II: investigations of mechanism

Abstract: BackgroundOlanzapine long-acting injection (LAI) is a salt-based depot antipsychotic combining olanzapine and pamoic acid. The slow intramuscular dissolution of this practically insoluble salt produces an extended release of olanzapine lasting up to 4 weeks. However, in a small number of injections (< 0.1%), patients experienced symptoms suggestive of olanzapine overdose, a phenomenon that has been termed "post-injection delirium/sedation syndrome" (PDSS). The authors conducted a series of parallel investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 14 publications
(28 reference statements)
5
90
1
5
Order By: Relevance
“…Unexpected high olanzapine plasma concentrations in people with PDSS led to the assumption that these would be responsible for the symptoms described; in particular, parallels with orally overdosed patients hinted at a connection in this manner [21]. Higher solubility of olanzapine pamoate monohydrate in plasma than solubility in muscle tissue was shown by McDonnell et al [34] and substantiated the hypothesis that false injections into the bloodstream lead to high concentrations of olanzapine in plasma and are thereby causative of PDSS. The mean time to onset of symptoms was 49 min, with a median of 25 min [23], which can be explained by the chemical features of olanzapine pamoate monohydrate salt and the fact that it has to dissolve first and then dissociate into its components olanzapine base and pamoic acid.…”
Section: Pharmacokinetics and Supposed Mechanismmentioning
confidence: 79%
See 3 more Smart Citations
“…Unexpected high olanzapine plasma concentrations in people with PDSS led to the assumption that these would be responsible for the symptoms described; in particular, parallels with orally overdosed patients hinted at a connection in this manner [21]. Higher solubility of olanzapine pamoate monohydrate in plasma than solubility in muscle tissue was shown by McDonnell et al [34] and substantiated the hypothesis that false injections into the bloodstream lead to high concentrations of olanzapine in plasma and are thereby causative of PDSS. The mean time to onset of symptoms was 49 min, with a median of 25 min [23], which can be explained by the chemical features of olanzapine pamoate monohydrate salt and the fact that it has to dissolve first and then dissociate into its components olanzapine base and pamoic acid.…”
Section: Pharmacokinetics and Supposed Mechanismmentioning
confidence: 79%
“…McDonnell et al [34] were able to closely follow up on 12 of the 30 cases reported by Detke et al [21] and detected elevated olanzapine concentrations in all of those patients. When collecting plasma samples at about six fixed time slots until resolution of the clinical symptoms, the initial concentrations within the first 6 h after injection never showed results below 100 ng/mL and would reach peak concentrations above 650 ng/mL.…”
Section: Pharmacokinetics and Supposed Mechanismmentioning
confidence: 94%
See 2 more Smart Citations
“…However, it remains unpredictable and is not thought to be related to the dose or dosing frequency or number of doses administered, or patient or medical factors (eg injection technique). 14,21 If it is to be used, olanzapine pamoate LAI should be initiated only for patients who have demonstrated response and tolerability to oral olanzapine. The SPC clearly states that the recommended starting doses and maintenance doses (after two months of treatment) of olanzapine LAI should be based on equivalent doses of oral olanzapine.…”
Section: Paliperidone Palmitate Lai (Xeplion ® )mentioning
confidence: 99%